129k views
3 votes
PLEASE HURRY!! 20 PTS!!

What are the solutions to the following system of equations? Select the correct answer below.
y = x2 − 4x + 3
2x + y = 6

a. (−1, 8) and (3, 0)
b. (−1, 3) and (8, 0)
c. (0, 8) and (3, −1)
d. (3, 8) and (−1, 0)

2 Answers

3 votes
B is the final answer!!! :)
User Kartheepan
by
5.8k points
2 votes
We have one of those equations already solved for y, so let's sub that one into the other one and solve the equation in terms of x only:
2x+( x^(2) -4x+3)=6. We will simplify that and at the same time bring the 6 over by subtraction to get a polynomial set to equal 0 that we can factor.
x^(2) -2x-3=0. We will factor that to get (x-3)(x+1) for x values of x = 3 and x = -1. a above is the choice that has the x values we need, -1 and 3.
User Eduardo Tolentino
by
4.7k points